Do Family Firms Provide More or Less Voluntary Disclosure? - CHEN, SHUPING; CHEN, XIA; CHENG, QIANG (Journal of Accounting Research, 2008)
ABSTRACT We examine the voluntary disclosure practices of family firms. We find that, compared to nonfamily firms, family firms provide fewer earnings forecasts and conference calls, but more earnings warnings. Whereas the former is consistent with family owners having a longer investment horizon, better monitoring of management, and lower information asymmetry between owners and managers, the higher likelihood of earnings warnings is consistent with family owners having greater litigation and reputation cost concerns. We also document that family ownership dominates nonfamily insider ownership and concentrated institutional ownership in explaining the likelihood of voluntary disclosure. Using alternative proxies for the founding family's presence in the firm leads to similar results.